Outage performance of SWIPT-NOMA-CR network with imperfect SIC and CSI - Zhuhua MA; Liping LUO (物联网学报)
For the cognitive relay network based on simultaneous wireless information and power transfer (SWIPT) and non-orthogonal multiple access (NOMA), which is termed as SWIPT-NOMA-CR network, considering the practical situation of imperfect successive interference cancellation (SIC) and channel state information (CSI), the outage performance of secondary users was studied by using three relay transmission schemes including ideal, time switching (TS) and power splitting (PS).The analytical expressions of outage probability were derived for the secondary users, and the theoretical derivations were validated by Monte Carlo simulations.The results show that the outage performance of secondary users is impaired due to the imperfect SIC and CSI.Compared with the imperfect CSI, the imperfect SIC causes more severe loss to the outage performance of the system.Moreover, the outage probability of PS relay transmission scheme is lower than that of TS scheme.When the imperfect SIC and CSI conditions are changed, the outage probability gap with PS scheme is less than that with TS scheme, which indicates that the reliability of PS relay transmission scheme is superior to that of TS scheme.